2003
DOI: 10.1034/j.1399-0004.2003.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Nine novel mutations in the protoporphyrinogen oxidase gene in Swedish families with variegate porphyria

Abstract: Variegate porphyria (VP) is an autosomal-dominant disorder that is caused by inheritance of a partial deficiency of the enzyme protoporphyrinogen oxidase (EC 1.3.3.4). It is characterized by cutaneous photosensitivity and/or various neurological manifestations. Protoporphyrinogen oxidase catalyses the penultimate step of haem biosynthesis, and mutations in the PPOX gene have been coupled to VP. In the present study, sequencing analysis revealed 10 different mutations in the PPOX gene in 14 out of 17 apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Interestingly, the same frameshift mutation has been previously described in Swedish VP patients [4]. The carriers showed different clinical symptoms and some were even asymptomatic, suggesting that there is no genotype-phenotype correlation for c.1330_1331delCT.…”
supporting
confidence: 54%
“…Interestingly, the same frameshift mutation has been previously described in Swedish VP patients [4]. The carriers showed different clinical symptoms and some were even asymptomatic, suggesting that there is no genotype-phenotype correlation for c.1330_1331delCT.…”
supporting
confidence: 54%
“…The prevalence of VP in Sweden has been estimated to be 1:100 000 and the mutation pattern in fourteen families has been reported [5]. Before the present study a total of 20 different mutations have been found among the Swedish VP patients (unpublished data).…”
Section: Introductionmentioning
confidence: 73%
“…The patients included in this study belong to five apparently unrelated Swedish families (Figure 1). The genetic analysis, that includes 845 nucleotides of the promoter region and the non-coding exon 1 of the PPOX gene, as well as the biochemical investigations used to identify patients and latent carriers have been previously described [5]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The prevalence of VP also varies between countries 12,13 but is mostly 0.5-1:100,000. [14][15][16] South Africa has a very high prevalence in the population of European origin (3:1000) which is also a consequence of a founder mutation. 17 The worldwide prevalence of HCP is not known.…”
Section: Acute Hepatic Porphyriamentioning
confidence: 99%